2020
DOI: 10.3389/fimmu.2019.03143
|View full text |Cite
|
Sign up to set email alerts
|

Store-Operated Calcium Entry via STIM1 Contributes to MRGPRX2 Induced Mast Cell Functions

Abstract: Mast cells are inflammatory immune cells that play an essential role in mediating allergic reactions in humans. It is well-known that mast cell activation is critically regulated by intracellular calcium ion (Ca 2+) concentrations. MAS-related G-protein coupled receptor-X2 (MRGPRX2) is a G-protein coupled receptor (GPCR) expressed on mast cells that is activated by various ligands, including several FDA approved drugs; consequently, this receptor has been implicated in causing pseudo-allergic reactions in huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 69 publications
0
18
0
Order By: Relevance
“…Ligand stimulation of MRGPRX2 induces exocytosis via the phospholipase Cβ/calcineurin pathway after intracellular Ca 2+ mobilization in MCs [ 14 , 42 ]. Store-operated Ca 2+ entry via stromal interaction molecule 1 could promote MRGPRX2-induced human MC response and Mrgprb2-dependent inflammation in a mouse model [ 43 ], supporting that the Ca 2+ mobilizing mechanism is an important signal for the physiological function of MRGPRX2. It is also known that phosphatidylinositol 3-kinase (PI3K)/AKT, MAPKs such as c-Jun N-terminal kinase (JNK), extracellular signal-regulated kinase 1/2 (Erk1/2), p38), and nuclear factor-κB (NF-κB) are involved in cytokine production from MCs during allergy [ 44 , 45 , 46 , 47 ].…”
Section: Mrgprx2mentioning
confidence: 99%
“…Ligand stimulation of MRGPRX2 induces exocytosis via the phospholipase Cβ/calcineurin pathway after intracellular Ca 2+ mobilization in MCs [ 14 , 42 ]. Store-operated Ca 2+ entry via stromal interaction molecule 1 could promote MRGPRX2-induced human MC response and Mrgprb2-dependent inflammation in a mouse model [ 43 ], supporting that the Ca 2+ mobilizing mechanism is an important signal for the physiological function of MRGPRX2. It is also known that phosphatidylinositol 3-kinase (PI3K)/AKT, MAPKs such as c-Jun N-terminal kinase (JNK), extracellular signal-regulated kinase 1/2 (Erk1/2), p38), and nuclear factor-κB (NF-κB) are involved in cytokine production from MCs during allergy [ 44 , 45 , 46 , 47 ].…”
Section: Mrgprx2mentioning
confidence: 99%
“…All three known Orai isoforms are expressed in human lung MCs and participate in FcϵRI-mediated activation ( 6 ). Moreover, in a human MC line, LAD2 cells, shRNA-mediated silencing of STIM-1 results in significant decrease in MRGPRX2-mediated Ca 2+ mobilization and degranulation ( 25 ). Given that STIM-1 couples to Orai1 for Ca 2+ influx ( 26 ), we hypothesized that this CRAC channel contributes to SP-induced responses in human MCs.…”
Section: Resultsmentioning
confidence: 99%
“…MRGPRX2 is a highly expressed GPCR in the DRG’s small-diameter neurons and is activated by CST-14 in a concentration-dependent manner [ 73 ]. Additionally, recent studies reported that CST-14 uses store-operated Ca 2+ entry via Stromal interaction molecule 1 (stim1) for MRGPRX2-induced MC activation, which leads to MC degranulation, Ca 2+ mobilization, and cytokine release in a concentration-dependent manner [ 104 ].…”
Section: Pharmacology Of Mas-related G Protein-coupled Receptors X 2 (Mrgprx2)mentioning
confidence: 99%